The absence of iron deficiency effect on the humoral immune response of piglets to tetanus toxoid - M. Svoboda; K. Nechvatalova; J. Krejci; J. Drabek; R. Ficek; M. Faldyna (Veterinární Medicína, 2007)
The aim of this study was to investigate an antibody response to tetanus toxoid in iron-deficient piglets. Ten piglets were not given any iron preparation until the age of 21 days. Ten piglets were given 200 mg Fe3+ dextran intramuscularly at the age of 3 days. All piglets were immunized with tetanus toxoid 14 days after birth. Reimmunization was performed 21 days after the first immunization. IgM and IgG titres were measured in weekly intervals after immunization. Haematological indices and iron concentration in the blood plasma of iron-deficient piglets characterized iron deficiency. The dynamic changes in IgM and IgG response to tetanus toxoid were similar in iron-deficient and iron-supplemented piglets and no significant differences in titres between the two groups were found in any period of the trial.